Preparation method and application of lithium-loving nanofiber interface layer on surface of copper current collector
The lithium-philic nanofiber interface layer on the copper current collector surface was prepared by electrospinning technology, and the CuO@F-OPAN nanofiber layer was formed by heat treatment, which solved the problems of uneven deposition of lithium ion and unsuitable SEI layer structure in lithium metal batteries, and achieved efficient cycling stability and Coulomb efficiency of lithium metal batteries.
Patent Information
- Application Number
- CN202510117820.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-24
AI Technical Summary
Existing lithium metal batteries have uneven lithium ion deposition on the electrode surface, unsuitable SEI layer structure composition, and serious problems in electrode volume expansion/shrinkage, resulting in unstable battery performance.
Electrospinning process was used to combine copper hydroxide and polymer matrix materials to prepare the lithium-philic nanofiber interface layer on the copper current collector surface. The CuO@F-OPAN nanofiber layer was formed by heat treatment, which was used as an artificial SEI film to regulate lithium deposition and SEI layer structure.
The uniform deposition of lithium ions is achieved, the growth of lithium dendrites is reduced, the mechanical properties and flexibility of the SEI film are enhanced, the volume changes during the cycle of the battery are buffered, and the cycle stability and Coulomb efficiency of the battery are improved.
Smart Images

Figure CN119913669A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and particularly relates to a preparation method and application of a lithium-philic nanofiber interface layer on the surface of a copper current collector. Background Art
[0002] With the popularity of new energy vehicles, people's demand for battery safety and high energy density is growing. Lithium metal has a high theoretical specific capacity (3860 mAh g −1 ) and extremely low redox potential (−3.040 V vs standard hydrogen electrode) are considered to be ideal negative electrode materials for high-energy-density batteries. Therefore, lithium metal batteries using metallic lithium as the negative electrode are expected to break through the energy density bottleneck of lithium-ion batteries at this stage and significantly improve the battery life in application scenarios such as mobile electronic terminals and electric vehicles. However, the inherent high reactivity of lithium metal causes it to spontaneously react with any non-aqueous electrolyte to form an ion-conducting and electronically insulating solid electrolyte interface (SEI) film when it comes into contact with any non-aqueous electrolyte. In order for lithium metal batteries to truly approach or meet the requirements of high energy density and high safety in the commercial field, the following problems still need to be solved: (1) How to improve the uneven deposition / stripping behavior of lithium ions on the electrode surface and avoid the formation and growth of lithium dendrites; (2) How to adjust the structural composition of the SEI layer generated on the electrode surface to enhance its affinity for lithium metal and achieve uniform lithium nucleation and growth behavior; (3) How to suppress the volume expansion / contraction of the electrode during the cycle and further promote the controllable construction of a uniform and stable SEI layer on the electrode surface. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a preparation method and application of a lithium-philic nanofiber interface layer on the surface of a copper current collector, so as to improve the uneven deposition / stripping behavior of lithium ions on the electrode surface, regulate the structural composition of the SEI layer, etc. Inorganic functional particles CuO particles can react with lithium to form beneficial Li2O components, while improving interface stability and ionic conductivity, and promoting uniform lateral deposition of lithium.
[0004] To this end, the present invention provides a method for preparing a lithium-philic nanofiber interface layer on the surface of a copper current collector, comprising: (1) adding copper hydroxide to a solvent and stirring and mixing uniformly, and then adding a polymer matrix material and stirring and mixing uniformly to obtain a spinning precursor solution; (2) electrospinning the spinning precursor solution to obtain a nanofiber membrane; and drying the nanofiber membrane by air blast drying and vacuum drying to obtain a nanofiber layer; (3) The nanofiber layer is heat treated and then cooled to room temperature to obtain a lithium-philic nanofiber interface layer on the surface of the copper current collector.
[0005] Preferably, in step (1), the mass ratio of copper hydroxide to polymer matrix material is (4-7): (10-20).
[0006] Preferably, in step (1), the polymer matrix material includes at least one of polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide and polydimethylsiloxane.
[0007] Preferably, in step (1), the polymer matrix material comprises polyacrylonitrile and polyvinylidene fluoride, and the mass ratio of polyacrylonitrile to polyvinylidene fluoride is (1-3): (0.5-1.5).
[0008] Preferably, in step (1), the solvent is N,N-dimethylformamide, and the mass ratio of copper hydroxide to the volume of the solvent is (0.42-0.8) g: (10-20) mL.
[0009] Preferably, the step (2), the electrospinning method comprises: wrapping the receiving roller of the electrospinning machine with copper foil, taking the spinning precursor solution into the needle tube and connecting the needle, adjusting the distance between the needle and the receiving roller to 10-15 cm; spinning for 1-3 h under the conditions of a needle tube advancement rate of 1-3 mL / h and a spinning voltage of 15-30 kV, to prepare a fiber membrane with a thickness of 20-30 μm and a width of 80-120 mm.
[0010] Preferably, in step (2), the forced air drying temperature is 50-80°C and the time is 5-8h; the vacuum drying temperature is 50-80°C and the time is 20-28h.
[0011] Preferably, in step (3), the heat treatment method comprises: placing the nanofiber layer in a Fresnel furnace, heating the temperature to 200-300°C at a heating rate of 1-3°C / min, heat treating for 1-3 h, and then naturally cooling to room temperature.
[0012] The present invention also provides application of the prepared lithium-philic nanofiber interface layer on the surface of the copper current collector in a battery.
[0013] Compared with the prior art, the advantages and positive effects of the present invention are as follows: the present invention provides a preparation method and application of a lithium-philic nanofiber interface layer on the surface of a copper current collector. The present application combines an organic polymer and an inorganic functional particle together through an electrospinning process, and the prepared lithium-philic nanofiber interface layer on the surface of a copper current collector has a three-dimensional nanofiber network structure, which can serve as a host for lithium deposition, can buffer the huge volume change during battery cycling, and improve the stability of the electrode / electrolyte interface; the polymer matrix has a high specific surface area and an interconnected pore structure, which can provide a convenient ion / electron transmission channel, balance the charge distribution on the surface of the lithium negative electrode during charging and discharging, and achieve a uniform lithium ion flux; the inorganic functional particle CuO particle can react with lithium to form a beneficial Li2O component, while improving the interface stability and ionic conductivity, promoting the uniform lateral deposition of lithium, and synergistically regulating the deposition behavior of metallic lithium.
[0014] The lithium-philic nanofiber interface layer on the surface of the copper current collector prepared in the present application can enhance the mechanical properties and flexibility of the SEI film to resist the destruction of lithium dendrites. In addition, the lithium-philic nanofiber interface layer on the surface of the copper current collector prepared in the present application can also promote the uniform deposition of lithium ions and reduce the growth of lithium dendrites.
[0015] After reading the specific embodiments of the present invention in conjunction with the accompanying drawings, other features and advantages of the present invention will become more clear. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the SEM image of the Cu(OH)2@PVDF-PAN nanofiber membrane of Example 1 of the present invention; Figure 2 This is the SEM image of the CuO@F-OPAN nanofiber membrane of Example 1 of the present invention; Figure 3 FTIR spectra of PVDF-PAN nanofiber membrane and F-OPAN nanofiber membrane of Example 2 of the present invention; Figure 4 Surface SEM images and cross-sectional SEM images of blank copper foil (Bare Cu) at different lithium deposition capacities; Figure 5 Surface SEM images and cross-sectional SEM images of CuO@F-OPAN nanofiber membranes at different lithium deposition capacities; Figure 6 This is one of the cycle performance test graphs of the lithium-copper battery of Example 3, Comparative Example 1, and Comparative Example 2 at different current densities and different lithium deposition capacities; Figure 7 The second graph is a cycle performance test graph of the lithium-copper battery of Example 3, Comparative Example 1 and Comparative Example 2 at different current densities and different lithium deposition capacities; Figure 8 The lithium copper battery of Example 3 at 1 mA cm -2 and 1 mAh cm -2 The charge and discharge curves of different cycle numbers under the conditions of ; Fig. 9 The lithium copper battery of Example 3 at 1 mA cm -2 and 1 mAh cm -2 Interface impedance test diagram of different cycle numbers under the condition of; Fig.10 The lithium-free negative electrode battery of Example 4 and Comparative Example 3 at 0.5 mA cm -2 The following cycle performance test diagram. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Meanwhile, after reading the present invention, those skilled in the art may make various modifications or changes to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
[0018] The method for preparing the lithium-philic nanofiber interface layer on the surface of a copper current collector of the present invention comprises: (1) adding copper hydroxide to a solvent and stirring and mixing uniformly, and then adding a polymer matrix material and stirring and mixing uniformly to obtain a spinning precursor solution; The mass ratio of copper hydroxide to polymer matrix material is (4-7):(10-20).
[0019] The polymer matrix material may include at least one of polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, and polydimethylsiloxane.
[0020] In this embodiment, the polymer matrix material includes polyacrylonitrile and polyvinylidene fluoride, and the mass ratio of polyacrylonitrile to polyvinylidene fluoride is (1-3): (0.5-1.5).
[0021] Preferably, the mass ratio of copper hydroxide to polymer matrix material is (4-5): (12-17), and the mass ratio of polyacrylonitrile to polyvinylidene fluoride is (1.5-2.5): (0.7-1.2); the lithium-philic nanofiber interface layer on the surface of the copper current collector can have a three-dimensional nanofiber network structure, which can serve as a host for lithium deposition, buffer the huge volume change during battery cycling, and improve the stability of the electrode / electrolyte interface; the polymer matrix has a high specific surface area and an interconnected pore structure, which can provide a convenient ion / electron transmission channel, balance the charge distribution on the surface of the lithium negative electrode during charging and discharging, and achieve uniform lithium ion flux; the inorganic functional particles CuO particles can react with lithium to form a beneficial Li2O component, while improving the interface stability and ionic conductivity, promoting the uniform lateral deposition of lithium, and synergistically regulating the deposition behavior of metal lithium. In addition, the mechanical properties and flexibility of the lithium-philic nanofiber interface layer on the surface of the copper current collector can also be enhanced to resist the destruction of lithium dendrites. In addition, the lithium-philic nanofiber interface layer on the surface of the copper current collector of the present application can also promote the uniform deposition of lithium ions and reduce the growth of lithium dendrites.
[0022] Polyvinylidene fluoride (PVDF) has good electrolyte wettability, high ionic conductivity, thermal stability and chemical stability. The melting point of PVDF is lower than the subsequent heat treatment process temperature, and PVDF can be in a molten state during the subsequent heat treatment process.
[0023] Polyacrylonitrile (PAN) contains a large number of polar groups and also has good thermal and chemical stability. PAN can undergo oxidative cyclization reaction during the subsequent heat treatment process to produce more polar groups on the surface.
[0024] The solvent is N, N-dimethylformamide, and the mass ratio of copper hydroxide to the volume of the solvent is (0.42-0.8) g: (10-20) mL, which can make the copper hydroxide and the polymer matrix material mixed evenly, so that the spinning precursor solution reaches a suitable viscosity, which is beneficial to the spinning of nanofibers, and can make the nanofibers evenly spun and there are no obvious droplets on the nanofiber membrane.
[0025] Preferably, the mass ratio of copper hydroxide to the volume ratio of the solvent is (0.42-0.5) g: (13-17) mL.
[0026] (2) electrospinning the spinning precursor solution to obtain a fiber membrane; and drying the fiber membrane by air blowing and vacuum drying to obtain a nanofiber membrane; The electrostatic spinning method comprises: wrapping a receiving roller of an electrostatic spinning machine with copper foil, taking a spinning precursor solution into a needle tube and connecting a needle, adjusting the distance between the needle tube and the receiving roller to 10-15 cm; spinning for 1-3 hours under the conditions of a needle tube advancement rate of 1-3 mL / h and a spinning voltage of 15-30 kV, and preparing a nanofiber membrane with a thickness of 20-30 μm and a width of 80-120 mm. The electrostatic spinning method of the present invention can be beneficial to the spinning of nanofibers, and can make the nanofibers uniform and without obvious droplets on the nanofiber membrane.
[0027] The blast drying temperature is 50-80°C and the time is 5-8h; the vacuum drying temperature is 50-80°C and the time is 20-28h. The organic solvent N,N-dimethylformamide DMF in the fiber membrane can be volatilized by blast drying and vacuum drying.
[0028] (3) The nanofiber membrane is heat treated and then cooled to room temperature to obtain a lithium-philic nanofiber interface layer on the surface of the copper current collector.
[0029] The heat treatment method comprises: placing the nanofiber membrane in a furnace, heating the temperature to 200-300°C at a heating rate of 1-3°C / min, heat treating for 1-3 hours, and then naturally cooling to room temperature. Preferably, the heat treatment temperature is 260-300°C, and the heat treatment is performed for 2-3 hours.
[0030] The nanofiber interface layer prepared by the present invention can be used to prepare batteries. Specifically, the nanofiber interface layer can be used as the negative electrode of the battery. The battery prepared by the nanofiber interface layer of the present invention has excellent electrochemical stability and cycle performance.
[0031] The advantages and positive effects of this application include: (1) Preparation of artificial SEI membrane based on lithium-philic CuO@F-OPAN nanofiber layer: This application uses electrospinning and heat treatment processes to effectively construct a lithium-philic CuO@F-OPAN nanofiber layer on the surface of copper foil to prepare an artificial SEI membrane. PVDF can be melted by heat treatment. The molten PVDF can be used as a pore size regulator or a physical linker to accelerate Li + The transmission of CuO@F-OPAN nanofiber layer can achieve close bonding between the copper foil and the lithium-philic CuO@F-OPAN nanofiber layer, effectively enhancing the interface stability and compatibility between the two, which is conducive to the long-term stable cycle of the battery.
[0032] (2) Regulation of lithium deposition / stripping behavior: Through heat treatment, polyacrylonitrile PAN can be converted into oxidized polyacrylonitrile OPAN rich in polar groups; oxidized polyacrylonitrile OPAN has excellent Li + affinity, which can make the Li +Flux homogenization helps to achieve uniform lithium deposition and avoid the growth of lithium dendrites.
[0033] Through the heat treatment process, the Cu(OH)2 particles can be in-situ converted into lithium-philic CuO particles, and the beneficial components formed by the redox reaction between the CuO particles and metallic lithium can be used to reduce the nucleation barrier of lithium, promote uniform lithium nucleation and growth behavior, and promote uniform lateral deposition of lithium, thereby synergistically regulating highly reversible lithium deposition / stripping behavior, and improving the coulombic efficiency and long-term cycle stability of the battery cycle. On this basis, the three-dimensional nanofiber network is used as a flexible support for the SEI film to buffer the volume deformation of the electrode during the battery cycle and enhance the interface stability, while guiding the uniform deposition of lithium from bottom to top and forming a stable interface layer rich in LiF and Li2O, thereby promoting the improvement of the electrochemical reversibility and stability of the lithium negative electrode.
[0034] (3) Regulation of SEI membrane structure and composition: Using a three-dimensional nanofiber network as a flexible support for the SEI membrane, and guiding the in-situ generation of the SEI membrane in the small gaps between the fibers, effectively suppressing the volume deformation of the electrode, giving the SEI membrane good structural stability and flexibility, thereby preventing the SEI membrane from breaking with the volume change of metallic lithium. Benefiting from the co-modification of CuO and PVDF, a stable and strong LiF- and Li2O-rich SEI interface layer is constructed in situ, which greatly promotes interfacial charge transfer, reduces parasitic reactions, and consolidates the electrode / electrolyte interface, which can be conducive to the rapid development of high-energy-density and high-safety lithium-free negative electrode batteries. Example 1
[0035] The method for preparing the lithium-philic nanofiber interface layer on the surface of the copper current collector of this embodiment comprises the following steps: (1) Preparation of spinning precursor solution: Weigh 0.45 g of copper hydroxide (Cu(OH)2), add it to 15 mL of N,N-dimethylformamide (DMF), stir, and ultrasonically treat the solution for 5 min. After the solution is evenly mixed, add 1 g of polyacrylonitrile (PAN) and 0.5 g of polyvinylidene fluoride (PVDF) to the above solution, stir in a constant temperature water bath at 60°C for 2 h until PAN and PVDF are completely dissolved, and obtain a spinning precursor solution.
[0036] (2) Preparation of nanofiber membrane by electrospinning: Cut a copper foil of 32 cm × 25 cm size to wrap the receiving roller of the electrospinning machine, take 3 mL of the above spinning precursor solution into the needle tube, connect the needle with a diameter of 800 μm, and adjust the receiving distance to 12 cm. Spin for 2 h under the conditions of needle tube propulsion rate of 1.5 mL / h and spinning voltage of 20 kV to prepare a nanofiber membrane with a thickness of 20-30 μm and a width of 90 mm. After air drying (60℃ air blowing for 6h) and vacuum drying (60℃ vacuum drying for 24h), Cu(OH)2@PVDF-PAN nanofiber membrane was obtained.
[0037] (3) Heat treatment A 10 cm×15 cm Cu(OH)2@PVDF-PAN nanofiber membrane was placed in a muffle furnace and heated to 260°C at a heating rate of 2°C / min. After heat treatment at 260°C for 2 h, it was naturally cooled to room temperature to obtain a lithium-philic nanofiber interface layer on the surface of the copper current collector, which was recorded as CuO@F-OPAN nanofiber membrane. Example 2
[0038] The method for preparing the nanofiber interface layer of this embodiment comprises the following steps: (1) Preparation of spinning precursor solution: 1 g of polyacrylonitrile (PAN) and 0.5 g of polyvinylidene fluoride (PVDF) were mixed and stirred in a constant temperature water bath at 60°C for 2 h until PAN and PVDF were completely dissolved to obtain a spinning precursor solution.
[0039] (2) Preparation of nanofiber membrane by electrospinning: Cut a 32 cm × 25 cm copper foil to wrap the receiving roller of the electrospinning machine, take 3 mL of the above spinning precursor solution into the needle tube, connect the needle with a diameter of 800 μm, and adjust the receiving distance to 12 cm. Spin for 2 h under the conditions of a needle tube propulsion rate of 1.5 mL / h and a spinning voltage of 20 kV to prepare a nanofiber membrane with a thickness of 20-30 μm and a width of 90 mm. After air drying (60℃ air blowing for 6h) and vacuum drying (60℃ vacuum drying for 24h), a PVDF-PAN nanofiber membrane was obtained.
[0040] (3) Heat treatment A 10 cm × 15 cm PVDF-PAN nanofiber membrane was placed in a muffle furnace and heated to 260 °C at a heating rate of 2 °C / min. After heat treatment at 260 °C for 2 h, it was naturally cooled to room temperature to obtain a lithium-philic nanofiber interface layer on the surface of the copper current collector, which was recorded as F-OPAN nanofiber membrane.
[0041] Figure 1This is a SEM image of the Cu(OH)2@PVDF-PAN nanofiber membrane of Example 1 of the present invention. The Cu(OH)2@PVDF-PAN nanofiber membrane is evenly distributed and there are no droplets on the fiber membrane.
[0042] Figure 2 This is a SEM image of the CuO@F-OPAN nanofiber membrane of Example 1 of the present invention. Since the heat treatment temperature is higher than the melting point of PVDF, PVDF will be in a molten state, and thus the nanofibers will be in a partially molten state.
[0043] Figure 3 The FTIR spectra of the PVDF-PAN nanofiber membrane and the F-OPAN nanofiber membrane of Example 2 of the present invention are shown in Figure 2. By comparing the infrared spectra before and after heat treatment, it can be seen that the infrared spectrum at 2245 cm −1 The peak band of C≡N decreases sharply and is between 1580 and 1650 cm −1 The C=O and C=N peaks at 2940 cm-1 increase sharply. −1 The number of nearby C-H bonds decreased, indicating that PAN underwent cyclization and partial oxidation after heat treatment.
[0044] Figure 4 The surface SEM images and cross-sectional SEM images of blank copper foil (Bare Cu) at different lithium deposition capacities are shown below. Figure 5 The surface SEM images and cross-sectional SEM images of CuO@F-OPAN nanofiber membranes at different lithium deposition capacities; after different capacities of lithium deposition, the fiber morphology of the nanofiber layer is still visible, and lithium is preferentially deposited under the nanofiber layer. As the lithium deposition capacity increases, the thickness of the lithium deposition layer also increases. Compared with Bare Cu and F-OPAN, the lithium deposition layer of CuO@F-OPAN is thinner and the lithium distribution is more uniform. In order to further observe the morphology of lithium deposition under the nanofiber layer, part of the surface nanofiber layer is removed after lithium deposition. Bare Cu presents an uneven lithium deposition morphology. In contrast, the CuO@F-OPAN nanofiber layer presents a uniform, dendrite-free, spherical lithium deposition morphology and a more uniform and smooth deposition surface. Example 3
[0045] The battery of this embodiment is a lithium copper battery, and the positive electrode of the lithium copper battery is a lithium sheet.
[0046] The copper foil loaded with CuO@F-OPAN nanofiber membrane in Example 1 was cut into 10 mm diameter discs as the negative electrode, the lithium sheet was used as the positive electrode, the polyethylene film with a diameter of 19 mm was used as the separator, and the battery was assembled with 80 μL of ether electrolyte. The ether electrolyte included 1.0 M lithium bistrifluoromethanesulfonyl imide (LiTFSI), 2 wt.% lithium nitrate (LiNO3) and a solvent, and the solvent included 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1. Example 4
[0047] The battery of this embodiment is a lithium-free negative electrode battery, and the positive electrode of the lithium-free negative electrode battery includes LiFePO4. Lithium iron phosphate (LiFePO4): conductive carbon black (Super P): PVDF are mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) is used as a solvent. The positive electrode slurry is prepared by grinding, and then the slurry is evenly scraped on the carbon-coated aluminum foil with a scraper. The coating thickness is 180μm, and after air drying (60℃ air blowing for 6h) and vacuum drying (60℃ vacuum drying for 24h), it is cut into a disc with a diameter of 10 mm as the positive electrode of the lithium-free negative electrode battery.
[0048] The copper foil loaded with CuO@F-OPAN nanofiber membrane of Example 1 was used as the negative electrode, the polyethylene membrane with a diameter of 16.5 mm was used as the separator, and the battery was assembled with 40 μL of ether electrolyte. The ether electrolyte included 1.0 M lithium bistrifluoromethanesulfonyl imide (LiTFSI), 2 wt.% lithium nitrate (LiNO3) and a solvent, and the solvent included 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1.
[0049] Comparative Example 1 The lithium-copper battery of this comparative example 1 is substantially the same as the lithium-copper battery of Example 3, except that the negative electrode of the lithium-copper battery of this comparative example 1 is copper foil.
[0050] Comparative Example 2 The lithium-copper battery of Comparative Example 2 is substantially the same as the lithium-copper battery of Example 3, except that the negative electrode of the lithium-copper battery of Comparative Example 2 is the F-OPAN nanofiber membrane of Example 2.
[0051] Comparative Example 3 The lithium-free negative electrode battery of this comparative example 3 is substantially the same as the lithium-free negative electrode battery of Example 4, except that the negative electrode of the lithium-free negative electrode battery of this comparative example 3 is copper foil.
[0052] Figure 6 This is one of the cycle performance test graphs of the lithium-copper battery of Example 3, Comparative Example 1, and Comparative Example 2 at different current densities and different lithium deposition capacities; Figure 7The second test graph of the cycle performance of the lithium copper battery of Example 3, Comparative Example 1 and Comparative Example 2 at different current densities and different lithium deposition capacities. At different current densities and different lithium deposition capacities, the cycle stability of CuO@F-OPAN is better than that of F-OPAN and Bare Cu. When the current density is 1 mA cm -2 , the deposition capacity of lithium is 1 mAh cm -2 When the CuO@F-OPAN is charged, it can maintain 230 stable cycles and the Coulombic efficiency remains above 98%.
[0053] Figure 8 The lithium copper battery of Example 3 at 1 mA cm -2 and 1 mAh cm -2 The charge and discharge curves of different cycle numbers under the conditions of ; The polarization voltage of CuO@F-OPAN did not increase significantly after 250 cycles, and the charge and discharge curves under different cycle numbers almost overlapped, showing good reversibility during the lithium deposition / stripping process.
[0054] Fig. 9 The lithium copper battery of Example 3 at 1 mA cm -2 and 1 mAh cm -2 The interface impedance test diagram of different cycle numbers under the conditions of 1 mA cm-2 and 1 mAh cm-2; the impedance of the lithium-copper battery loaded with CuO@F-OPAN did not change much after 150 cycles, forming a stable SEI layer.
[0055] Fig.10 The lithium-free negative electrode battery of Example 4 and Comparative Example 3 at 0.5 mA cm -2 The cycling performance test diagram shows that the lithium-free negative electrode battery loaded with CuO@F-OPAN can maintain a capacity of 49.2% after 100 cycles at 0.5 C, and the average coulombic efficiency can reach 99.3%.
[0056] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A method for preparing a lithium-philic nanofiber interface layer on the surface of a copper current collector, characterized in that: include: (1) adding copper hydroxide to a solvent and stirring and mixing uniformly, and then adding a polymer matrix material and stirring and mixing uniformly to obtain a spinning precursor solution; (2) electrospinning the spinning precursor solution to obtain a nanofiber membrane; and drying the nanofiber membrane by air blast drying and vacuum drying to obtain a nanofiber layer; (3) The nanofiber layer is heat treated and then cooled to room temperature to obtain a lithium-philic nanofiber interface layer on the surface of the copper current collector.
2. The method for preparing the lithium-philic nanofiber interface layer on the surface of the copper current collector according to claim 1, characterized in that: In the step (1), the mass ratio of copper hydroxide to polymer matrix material is (4-7): (10-20).
3. The method for preparing the lithium-philic nanofiber interface layer on the surface of the copper current collector according to claim 1, characterized in that: In the step (1), the polymer matrix material includes at least one of polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide and polydimethylsiloxane.
4. The method for preparing the lithium-philic nanofiber interface layer on the surface of the copper current collector according to claim 3, characterized in that: In step (1), the polymer matrix material includes polyacrylonitrile and polyvinylidene fluoride, The mass ratio of polyacrylonitrile to polyvinylidene fluoride is (1-3):(0.5-1.5).
5. The method for preparing the lithium-philic nanofiber interface layer on the surface of the copper current collector according to claim 1, characterized in that: In step (1), the solvent is N,N-dimethylformamide, The mass ratio of copper hydroxide to the volume ratio of the solvent is (0.42-0.8) g: (10-20) mL.
6. The method for preparing the lithium-philic nanofiber interface layer on the surface of the copper current collector according to claim 1, characterized in that: The step (2) comprises the following steps: wrapping a receiving roller of an electrospinning machine with copper foil, taking a spinning precursor solution into a needle tube and connecting the needle, and adjusting the distance between the needle and the receiving roller to 10-15 cm; The spinning time was 1-3 h at a needle tube propulsion rate of 1-3 mL / h and a spinning voltage of 15-30 kV to prepare a fiber membrane with a thickness of 20-30 μm and a width of 80-120 mm.
7. The method for preparing a lithium-philic nanofiber interface layer on a copper current collector surface according to claim 1, characterized in that: In step (2), the blast drying temperature is 50-80°C and the time is 5-8h; The vacuum drying temperature is 50-80°C and the time is 20-28h.
8. The method for preparing a lithium-philic nanofiber interface layer on a copper current collector surface according to claim 1, characterized in that: The heat treatment method in step (3) comprises: placing the nanofiber layer in a Fresnel furnace, heating the temperature to 200-300°C at a heating rate of 1-3°C / min, and naturally cooling the nanofiber layer to room temperature after heat treatment for 1-3 hours.
9. Use of the lithium-philic nanofiber interface layer on the surface of a copper current collector prepared according to any one of claims 1 to 8 in a battery.
Citation Information
Patent Citations
Preparation method and application of porous sheet capable of blocking UV and VOC
CN111155190A
Carbon-based azide film suitable for MEMS (Micro Electro Mechanical System) micro-charge and preparation method of carbon-based azide film
CN116288935A
High-molecular polymer copper azide compound as well as preparation method and application thereof
CN116479646A
Pressure-sensitive material based on copper metal-organic framework, preparation method and sensor
CN117188157A
Surfactant-assisted synthesis of surface-functionalized nanoparticle-polymer electrospun composites
US20190002309A1